Procedure for ensuring unity of judicial practice in the Russian Federation - P.V. Korshunova (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2024)
Background. The article substantiates the real need to develop a mechanism for ensuring the unity of judicial practice, reveals the procedure and problematic aspects of its implementation. The mechanism for ensuring the unity of judicial practice is based on the need for judges to strictly comply with regulatory legal acts and follow the legal positions of the highest judicial bodies, including elements of judicial doctrine. Based on the existing problems, it was concluded that it is necessary to change the current legislation. The purpose of the study is to offer a scientific substantiation of the mechanism for ensuring the unity of judicial practice, to identify problems in its application and to suggest a direction for improving the current legislation. Materials and methods. The article used the formal legal method, systemic and comparative legal method, statistical method, methods of analysis and synthesis. Results. Based on the study, a conclusion was made about the importance of the mechanism for ensuring the unity of judicial practice in the Russian Federation; the need to make changes to the current legislation was identified; some directions for such changes have been proposed. Conclusions. The study of possible ways to ensure the unity of judicial practice allowed us to state that at the moment it is necessary to develop a unified concept of a mechanism for ensuring the unity of judicial practice through the formulation of its concept and functioning. The identified problems made it possible to formulate directions for improving the current legislation in order to further strengthen the unity of judicial practice in the legal system of the Russian Federation.